Tinjauan Pengadaan Bahan Pustaka di Perpustakaan Fakultas Ekonomi Universitas Negeri Padang - Susanti, Nofrila; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was: (1) describe how the procurement of library materials, (2) the constraints in the procurement of library materials, and (3) efforts to overcome the obstacles faced in the procurement of library materials in the Library of the Faculty of Economics, State University of Padang. Research methodology is a qualitative method, namely by describing the date relating to the procurement of library materials in the Library of the Faculty of Economics, State University of Padang. Date obtained through direct observation and interview techniques with library employees. From the discussion, found three of the following. First, the procurement of library materials: (a) the procurement procedure is to take stock of library books to the library possessed by submitting a letter to Prodi to request a list of what books are needed study program at the Faculty of Economics. After that, the list of books needed by the library are sent to the Assistant Dean (World War I) to be approved procurement of library materials, (b) sources of procurement of library materials only by purchase and gift, (c) the selection of library materials is done by asking syllabus used to teach a course lecturer, view the catalog publisher and is based on a book that is widely used by students. Second, constraints that limited funds to procure, ordered books often have limited stock of books, and employee education background is only one library. Third, efforts to overcome the obstacles that raise funds by collecting fines that students who are late returning books, copy books owned by the lecturers to supplement library materials, and provide training for staff in the field of library educational background is not a library. Keywords: procurement of library materials; stock of library books; library materials